Macroevolution with living and fossil species - Guillerme, Thomas (Trinity College (Dublin, Ireland). Department of Zoology, 2015)
Although many biodiversity studies focus on living species, the vast majority of species that ever lived are long extinct. It is therefore crucial to combine data from both living and fossil species to fully understand macroevolutionary patterns and processes. This thesis focuses on ways to combine both living and fossil taxa into phylogenies and investigates how the resulting phylogenies can be used to investigate macroevolutionary questions.
Keywords: Zoology, Ph.D.; Ph.D. Trinity College Dublin.